Analysis of Consumer Considerations Regarding Disaster Risk in Making Residential Choice Decisions in Padang City - Arbi, Rustian; Ophiyandri, Taufika; Hidayat, Benny (Universitas Negeri Padang, 2024)
Considering that the city of Padang is the capital city of West Sumatra province which apart from being the center of government, is also the center for economic activities, education, trade and other informal sectors, the need for housing for the community needs attention. Because proper housing is a basic need for humans to carry out life and daily activities. The geographical condition of the city of Padang is in the area along the earthquake path following the 6,500 km subduction zone to the west of Sumatra Island. Apart from earthquakes, there are many disasters that have the potential to occur in the city of Padang such as tsunamis, landslides, floods, flash floods, tornadoes, and others. These potential disasters must be considered by consumers in making decisions in choosing housing that is appropriate and has a small disaster risk. The purpose of this research is to identify the reasons for consumers in making decisions about choosing housing in the city of Padang and also to analyze consumer considerations regarding disaster risk in making decisions about choosing housing in the city of Padang. The study was conducted on 60 respondents with 33 indicators which were divided into six general variables, namely price, location, building architecture, ease of transportation, environmental facilities and infrastructure and psychology then two disaster risk variables, namely disaster-free locations and building structures. In this study, the most influential variables in consumer decision making in choosing housing in the city of Padang sequentially were disaster-free locations, building structures, building architecture, environmental facilities and infrastructure, psychology, price, location and ease of transportation. And also the six general variables regarding consumer considerations in making decisions on choosing housing in Padang City simultaneously or as a whole have an influence on the two disaster risk variables studied, namely disaster-free locations and building structures.